Chinese herbal compounds containing scorpion in the treatment of epilepsy: A protocol for systematic review and meta-analysis. Issue 10 (12th March 2021) - Rong, Ping; Fu, Qianfang; Zhang, Xilian; Liu, Xuan; Yang, Jie; Wang, Xin; Wang, Shuai; Liu, Hui; Ma, Rong; Nie, Lianghui; Ma, Rong
Abstract: Background: Epilepsy is 1 of the common neurodevelopmental diseases. It can affect about 0.5% to 1.0% of the population regardless of their race and social class. Despite the development of a wide range of treatments, there remaining about one-third of patients still experience seizures. Chinese herbal compounds containing scorpion (CHCCS) have shown an outstanding curative effect on nerve protection and epilepsy. But there's no study to assess its clinical efficacy and safety. Methods: Each data of CHCCS in treating epilepsy from related English and Chinese databases will be searched. The primary outcome is the efficacy of the CHCCS on epilepsy. And the secondary outcomes include recurrence rate and side effects. The risk of bias will be assessed, and RevMan5.3 and Stata14.0 will be performed for meta-analysis. Finally, we will assess the level of the resulting evidence. Results: The results of the study will be combined with current evidence and published in a peer-reviewed journal. Conclusions: This study will specifically investigate the effectiveness and safety of CHCCS in treating epilepsy. INPLASY registration number: INPLASY202120056.